Facies analysis and depositional model of the middle-upper triassic Semantan formation, Central Pahang, Malaysia - Muhammad Azfar, Mohamed; Mazshurraiezal, Nasir; Mohd Syukri, Said; Meng, Choongchee; Mohamad Shaufi, Sokiman; Nur Asyraf, Md Akhir; Muhammad Aslam, Md Yusof; Muhammad Noor Amin, Zakariah; Mohd Nizam, Abdul Rashid; Salahuddin, Husein; Noorzamzarina, Sulaiman; Afiq Naim, Mohd (Penerbit UTM Press, 2022)
This study details the sedimentological analysis of the Middle-Upper Triassic Semantan Formation in the Jerantut-Temerloh-Kemayan region of central Pahang. Seven (F1-7) facies have been identified which are; F1) poorly sorted conglomerate, F2) pebbly sandstone, F3) structureless-to-parallel laminated sandstone, F4) wavy-to-ripple fine-to-medium laminated sandstone, F5) slumped thin-interbeded sandstone and shale, F6) interbedded sandstone and shale, and F7) shale, represent a subordinate part of the Semantan Formation. Examination of the succession of the vertical facies resulted in concession of genetic units (FA1-FA5) which are; FA1) deep channel complex, FA2) distal lobe, FA3) hybrid gravity flow deposit, FA4) channelised lobe and FA5) non-channelised lobe. It is believed that these five genetic units were deposited within four proposed laterally contiguous depositional environments which are; 1) Inner fan - deep channel-levee complex (represent by FA1), 2) Mid fan - channelised lobe (represented by FA5 and FA3), 3) Mid Fan - non-channelised lobe (represented by FA4 and FA3), and 4) Outer fan - distal lobe (represented by FA2). The Semantan Formation deep-water fan is analysed as a sand-rich fan system, based on its sediment types.